Boron nitride nanometer local gel electrolyte, zinc ion battery and preparation method

By introducing hydroxylated boron nitride sheets into the gel electrolyte of zinc ion battery, a local hydrophobic area is formed, which solves the problem of side reactions of zinc ion battery in aqueous electrolyte and the growth of zinc dendrites, and improves the cycle stability of the battery.

CN119695303AActive Publication Date: 2025-03-25CHENGDU TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411807796.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-25
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Existing zinc-ion batteries are prone to side reactions and zinc dendrites growth when using aqueous electrolytes, which affects the cycle life of the battery.

Method used

Using gel electrolyte containing boron nitride nanosheets, a local hydrophobic region is formed by introducing hydroxylated boron nitride sheets into the gel, reducing the contact between zinc electrodes and water molecules, and inhibiting side reactions and the growth of zinc dendrites.

Benefits of technology

It effectively reduces the occurrence of side reactions, inhibits the growth of zinc dendrites, and improves the circulation stability and material uniformity of zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695303A_ABST
    Figure CN119695303A_ABST
Patent Text Reader

Abstract

The invention discloses a boron nitride nanometer local gel electrolyte, a zinc ion battery and a preparation method. Belongs to the technical field of zinc ion batteries. The preparation method comprises the following steps: adding a monomer, a zinc salt, an initiator, a cross-linking agent and a catalyst into a hydroxylated boron nitride nanosheet aqueous dispersion with the mass concentration of 0.1-0.3 mg / mL, adjusting the pH value to 4.0-5.0 to obtain a gel pre-polymerization solution, and heating and polymerizing the pre-polymerization solution at 35-45 DEG C to obtain the boron nitride nano local gel electrolyte. According to the preparation method, hydroxylated boron nitride sheets with a specific proportion can be successfully introduced into gel containing zinc salt, a local hydrophobic region is formed in the gel, contact between a zinc electrode and water molecules is reduced, side reactions are avoided, and growth of zinc dendrites is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc ion batteries, in particular to a zinc ion battery containing a gel electrolyte containing boron nitride nanomaterials. Background Art

[0002] Zinc-ion batteries have the advantages of high volumetric energy density, low redox potential, high abundance and environmental friendliness. They are an emerging battery product with great development prospects.

[0003] Existing zinc-ion batteries usually use aqueous electrolytes, which are prone to a variety of side reactions caused by water, such as hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). There is also the phenomenon of zinc dendrites caused by uneven deposition and / or stripping of zinc ions on the negative electrode, resulting in a rough and uneven electrode surface. The growth of zinc dendrites also further increases the surface area of ​​the zinc negative electrode, promotes the occurrence of side reactions, and seriously affects the cycle life of the battery.

[0004] To solve the above problems, some existing technologies have constructed artificial interface layers on the surface of zinc negative electrodes, such as inorganic nano-calcium carbonate coatings, organic polyimide coatings, and artificial polyacrylonitrile coatings. However, the thickness of these interface layers is difficult to control, the preparation process is complicated, and the cost is high, which is not suitable for large-scale mass production; some other existing technologies have adopted electrolyte composition optimization, such as additive regulation, solvation, or salt-in-water improvements. However, the addition of additives and / or salts not only increases the cost of the electrolyte, but also increases the viscosity of the electrolyte, significantly reducing the ionic conductivity. Summary of the invention

[0005] In view of the defects of the prior art, the purpose of the present invention is to propose a boron nitride nanogel electrolyte and a zinc ion battery and a preparation method. The electrolyte successfully introduces hydroxylated boron nitride sheets into a gel containing zinc salts. While maintaining a relatively high ionic conductivity, a localized hydrophobic area can be formed inside the gel, thereby reducing the contact between the zinc electrode and water molecules, avoiding the occurrence of side reactions, and inhibiting the growth of zinc dendrites.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a boron nitride nano-localized gel electrolyte comprises the following steps:

[0008] (1) mixing hydroxylated boron nitride nanosheets with water and uniformly dispersing them by ultrasonication to obtain a hydroxylated boron nitride dispersion having a mass concentration of 0.1-0.3 mg / mL;

[0009] (2) adding monomers, zinc salt, initiator, crosslinking agent and catalyst to the hydroxyboron nitride dispersion to obtain a mixed solution, and adjusting the pH of the mixed solution to 4.0-5.0 to obtain a gel prepolymer solution;

[0010] (3) heating the gel prepolymer solution to polymerize at 35-45° C. to obtain the boron nitride nano-localized gel electrolyte;

[0011] Wherein, the monomer is selected from one or more of acrylamide, acrylic acid, methacrylic acid, acryloyloxyethyltrimethylammonium chloride, and 2-acrylamide-2-methylpropanesulfonic acid, and the concentration of the zinc salt is 0.5-2 mol / L.

[0012] The electrolyte obtained by the present invention is in a gel state, wherein uniformly dispersed hydroxylated boron nitride nanosheets with excellent mechanical properties and insulation and a specific dispersion concentration are successfully introduced, which can not only improve the mechanical properties of the gel electrolyte, enhance its insulation, and avoid battery short circuit due to electronic conduction, but also realize the stable dispersion of the hydroxylated boron nitride nanosheets in the polymer aqueous solution and the formation of nano local hydrophobic areas in the gel through the local hydrophilicity of the hydroxyl groups contained in the edges of the hydroxylated boron nitride nanosheets and the local hydrophobicity of the internal plane, thereby reducing the contact between the zinc electrode and water molecules, reducing side reactions, inhibiting the growth of zinc dendrites, and enhancing the uniformity of the material.

[0013] According to some preferred embodiments of the present invention, the zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc acetate, zinc nitrate and zinc perchlorate.

[0014] According to some preferred embodiments of the present invention, the initiator is ammonium persulfate and / or potassium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide and / or ethylene glycol diacrylate.

[0015] According to some preferred embodiments of the present invention, the mass of the monomer is 10-20 wt % of the mass of the gel prepolymer solution.

[0016] The inventors unexpectedly discovered that under this mass ratio, the water content of the gel electrolyte is moderate and the polymerization molding effect is good.

[0017] According to some preferred embodiments of the present invention, the monomers include anionic monomers, cationic monomers and acrylic monomers, wherein the anionic monomer is 2-acrylamide-2-methylpropane sulfonic acid, the cationic unit is acryloyloxyethyltrimethylammonium chloride, and the acrylic monomer is one or more of acrylamide, acrylic acid, and methacrylic acid.

[0018] According to the above preferred embodiments, the gel electrolyte obtained by the present invention is a polyzwitterionic gel electrolyte introduced with hydroxyboron nitride nanosheets, which can further form a dual ion channel through the polyzwitterionic network, regulate the transmission path of zinc ions, limit the two-dimensional diffusion of zinc ions, enhance the uniform deposition and stripping of zinc ions on the surface of the zinc negative electrode, further inhibit the growth of zinc dendrites, and extend the battery cycle life.

[0019] According to some preferred embodiments of the present invention, the hydroxylated boron nitride nanosheets are obtained by ball-milling micron-sized boron nitride powder with an aqueous sodium hydroxide solution, washing the product obtained by ball milling with water, ultrasonically dispersing and centrifuging it, and then freeze-drying it to obtain the hydroxylated boron nitride powder having a particle size of 150-250 nm.

[0020] According to some preferred embodiments of the present invention, the temperature of the heating polymerization is 40° C. and the time is 6-12 hours.

[0021] According to some preferred embodiments of the present invention, the pH is adjusted by the content of the catalyst, and the catalyst is N,N,N',N'-tetramethylethylenediamine.

[0022] The inventors unexpectedly discovered that the preferred catalyst can not only effectively catalyze the free radical polymerization reaction, but also simultaneously adjust the pH of the prepolymerization system and extend the cycle life of the battery.

[0023] The present invention further provides a boron nitride nano-localized gel electrolyte prepared according to the above preparation method.

[0024] The electrolyte is composed of a three-dimensional network of nanocomposite copolymers formed by in-situ polymerization of hydroxylated boron nitride nanosheets and three monomers. The hydroxylated boron nitride nanosheets can not only form local hydrophobic areas in the three-dimensional network, but also the hydrogen bonds formed with the three-dimensional network can serve as a second layer of physical cross-linking network.

[0025] The present invention further provides a zinc ion battery containing the boron nitride nano-localized gel electrolyte.

[0026] The present invention has the following beneficial effects:

[0027] (1) In the gel electrolyte of the present invention, the hydroxylated boron nitride nanosheets have excellent mechanical properties and insulation properties, which can improve the safety performance of the gel electrolyte. The hydroxylated boron nitride nanosheets form dispersed nano-local hydrophobic regions inside the gel electrolyte, which reduces the direct contact between the zinc electrode and water molecules, reduces the occurrence of side reactions, and inhibits the growth of zinc dendrites.

[0028] (2) In some preferred embodiments, the preparation method of the present invention introduces a specific concentration of hydroxylated boron nitride nanosheets into a ternary copolymer network structure formed by copolymerization of anionic monomers, cationic monomers, and acrylic monomers. The hydroxylated boron nitride nanosheets can form hydrogen bonds with the amide groups, carboxyl groups, and sulfonic acid groups in the polymer network, thereby improving the mechanical properties of the gel electrolyte.

[0029] (3) The electrolyte of the present invention can be prepared by a one-step method, the preparation process is simple, the reaction conditions are mild, and the cost is low, safe and reliable, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The symmetric battery with the gel electrolyte prepared in Example 1 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0031] Figure 2 The symmetric battery with the gel electrolyte prepared in Example 2 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0032] Figure 3 The symmetric battery with the gel electrolyte prepared in Example 3 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0033] Figure 4 The symmetric battery with the gel electrolyte prepared in Example 3 was -2 Current density and 5mAh cm -2 Cycling performance diagram at capacity density.

[0034] Figure 5 The Zn-Cu battery with the gel electrolyte prepared in Example 3 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0035] Figure 6 The symmetric battery with the gel electrolyte prepared in Comparative Example 1 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0036] Figure 7 It is a comparison chart of the mechanical properties test of the gel electrolyte of comparative example 1 and example 3.

[0037] Figure 8 The liquid symmetrical battery prepared in Comparative Example 2 has a -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0038] Fig. 9 The liquid symmetrical battery prepared in Comparative Example 2 was-2 Current density and 5mAh cm -2 Cycling performance diagram at capacity density.

[0039] Fig.10 The liquid Zn-Cu battery prepared in Comparative Example 2 was -2 Current density and 1mAh cm -2 Cycling performance diagram at capacity density.

[0040] Fig.11 It is a comparison diagram of the cyclic voltammetry test curves of the Zn-Cu battery of Comparative Example 2 and Example 3. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0042] Example 1

[0043] Hydroxylated boron nitride nanosheets were obtained by the following process: 100 mg of micron-sized boron nitride powder and 2 mol / L sodium hydroxide aqueous solution were placed in a ball mill, and zirconium dioxide grinding balls were added, with a ball-to-material ratio of 50:1. The rotation speed was set to 200 rpm, and the mixture was ground for 30 hours. After ball milling, the product was washed with deionized water until the pH value was close to neutral. Dispersed in water at a concentration of 0.5 mg / mL and ultrasonically treated for 1 hour, the ultrasonic dispersion solution was centrifuged at 1000 rpm for 10 minutes to remove agglomerates and thick sheets. Finally, the dispersion was freeze-dried to obtain hydroxylated boron nitride nanosheets. The microscopic morphology of the hydroxylated boron nitride nanosheets was characterized by scanning electron microscopy, and its surface was relatively flat and the size was about 200 nm.

[0044] Furthermore, the boron nitride nano-localized gel electrolyte was prepared by the following process:

[0045] 1.5 mL of pure water was measured in a reaction bottle, and hydroxylated boron nitride nanosheets were added, and the mixture was placed in an ultrasonic cleaning machine for 30 min to allow for thorough mixing, thereby obtaining a hydroxylated boron nitride nanosheet dispersion with a mass concentration of 0.1 mg / mL;

[0046] Weigh 0.05 g of 2-acrylamido-2-methyl-1-propane sulfonic acid and add it to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, add 16 μL of tetramethylethylenediamine to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, add 0.861 g of zinc sulfate to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 5 min, add 0.25 g of acrylamide to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, continue to add 0.2 mL of acryloyloxyethyltrimethylammonium chloride to the bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, then add 6 mg of ammonium persulfate and 40 μL of N,N'-methylenebisacrylamide solution, put it into an ultrasonic cleaner and mix it evenly for 1 min to obtain a prepolymer solution;

[0047] The prepolymer solution was transferred into a glass mold and placed in an oven, and a free radical polymerization reaction was carried out at 40° C. for 6 hours to obtain a boron nitride nano-localized gel electrolyte.

[0048] The boron nitride nano-localized gel electrolyte prepared in this example was assembled into a Zn-Zn symmetrical battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 1 As shown, it can be seen that at 1 mA cm -2 The current density is 1 mAh cm -2 At the capacity density, the symmetrical battery can be cycled stably for about 600 hours. The surface gel electrolyte effectively inhibits the growth of zinc dendrites and has good cycle stability.

[0049] Example 2

[0050] The same hydroxylated boron nitride nanosheets as in Example 1 were used to prepare boron nitride nano-localized gel electrolyte by the following process:

[0051] 1.5 mL of pure water was measured in a reaction bottle, and hydroxylated boron nitride nanosheets were added, and the mixture was placed in an ultrasonic cleaning machine for 30 min to allow the mixture to be fully mixed, thereby obtaining a hydroxylated boron nitride nanosheet dispersion with a mass concentration of 0.3 mg / mL;

[0052] Weigh 0.05 g of 2-acrylamido-2-methyl-1-propane sulfonic acid and add it to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, weigh 16 μL of tetramethylethylenediamine and add it to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, continue to add 0.861 g of zinc sulfate to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 5 min, weigh 0.25 g of acrylamide and add it to the reaction bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, continue to add 0.2 mL of acryloyloxyethyltrimethylammonium chloride to the bottle, put it into an ultrasonic cleaner and mix it evenly for 1 min, then add 6 mg of ammonium persulfate and 40 μL of N,N'-methylenebisacrylamide solution, put it into an ultrasonic cleaner and mix it evenly for 1 min to obtain a prepolymer solution;

[0053] The prepolymer solution was transferred into a glass mold and placed in an oven to perform free radical polymerization at 40° C. for 6 hours to obtain the boron nitride nano-localized gel electrolyte.

[0054] The boron nitride nano-localized gel electrolyte prepared in this example was assembled into a Zn-Zn symmetrical battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 2 As shown, it can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At the capacity density, the symmetrical battery can be stably cycled for about 700 hours. The surface gel electrolyte effectively inhibits the growth of zinc dendrites and has good cycle stability.

[0055] Example 3

[0056] The same hydroxylated boron nitride nanosheets as in Example 1 were used to prepare boron nitride nano-localized gel electrolyte by the following process:

[0057] 1.5 mL of pure water was measured in a reaction bottle, and hydroxylated boron nitride nanosheets were added, and the mixture was placed in an ultrasonic cleaning machine for 30 min to fully mix the mixture to obtain a hydroxylated boron nitride nanosheet dispersion with a mass concentration of 0.2 mg / mL;

[0058] Weigh 0.05g of 2-acrylamido-2-methyl-1-propane sulfonic acid and add it to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, take 16μL of tetramethylethylenediamine and add it to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, continue to add 0.861g of zinc sulfate to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 5min, take 0.25g of acrylamide and add it to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, continue to add 0.2mL of acryloyloxyethyltrimethylammonium chloride to the bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, then add 6mg of ammonium persulfate and 40μL of N,N'-methylenebisacrylamide solution, put it in an ultrasonic cleaner and mix it evenly for 1min to obtain a prepolymer solution;

[0059] The prepolymer solution was transferred into a glass mold and placed in an oven, and free radical polymerization was performed at 40°C for 6 hours to obtain the boron nitride nano-localized gel electrolyte. The boron nitride nano-localized gel electrolyte prepared in this example was assembled into a Zn-Zn symmetrical battery and the electrochemical cycle stability performance test was performed. Figure 3 and Figure 4 As shown, from Figure 3 It can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At the same capacity density, the symmetrical battery can be stably cycled for 1100 hours, indicating that the gel electrolyte effectively inhibits the growth of zinc dendrites and has good cycle stability. Figure 4 It can be seen that even at 5mAcm -2 The current density and 5 mAh cm -2 At the same capacity density, the symmetrical battery can also be stably cycled for 350 hours, indicating that the gel electrolyte also has good cycle stability under large current.

[0060] The boron nitride nano-localized gel electrolyte prepared in this example was assembled into a Zn-Cu battery for electrochemical performance testing. The test results are shown in FIG. Figure 5 As shown, it can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At the capacity density, the Zn-Cu battery can be cycled stably for 45 hours. After 45 hours, the battery loses stability due to the growth of zinc dendrites and side reactions. Calculation shows that the coulombic efficiency of the Zn-Cu battery after 130 cycles is 99.24%.

[0061] Comparative Example 1

[0062] Weigh 0.05g of 2-acrylamido-2-methyl-1-propane sulfonic acid and add it to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, take 16μL of tetramethylethylenediamine and add it to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, continue to add 0.861g of zinc sulfate to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 5min, take 0.25g of acrylamide and add it to the reaction bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, continue to add 0.2mL of acryloyloxyethyltrimethylammonium chloride to the bottle, put it in an ultrasonic cleaner and mix it evenly for 1min, adjust the amount of catalyst tetramethylethylenediamine to make the pH to about 4, then add 6mg of ammonium persulfate and 40μL of N,N'-methylenebisacrylamide solution, put it in an ultrasonic cleaner and mix it evenly for 1min to obtain a prepolymer solution;

[0063] The prepolymer solution was transferred into a glass mold and placed in an oven to undergo a free radical polymerization reaction at 40° C. for 6 hours to obtain a gel electrolyte free of hydroxylated boron nitride nanosheets.

[0064] The gel electrolyte prepared in this comparative example was assembled into a Zn-Zn symmetrical battery and subjected to an electrochemical cycle stability performance test. The test results are shown in FIG. Figure 6 As shown, it can be seen that at 1 mA cm -2 The current density and 1 mAh cm -2 At the capacity density, the symmetrical battery can be stably cycled for about 300 hours, which is much shorter than the cycle time of the symmetrical battery in Examples 1-3, indicating that the nano-hydrophobic domains formed after the addition of hydroxylated boron nitride nanosheets can effectively inhibit the growth of zinc dendrites, thereby improving the cycle stability of the battery.

[0065] Furthermore, the mechanical properties of the gel electrolyte of comparative example 1 without hydroxylated boron nitride nanosheets and the boron nitride nano-localized gel electrolyte of example 3 were tested and compared. The test results are as follows: Figure 7 As shown, it can be seen that after the addition of hydroxylated boron nitride nanosheets, the tensile strength and elongation at break of the local gel electrolyte are significantly improved, indicating that the hydrogen bonding between hydroxylated boron nitride nanosheets and the polymer network can effectively increase the energy dissipation of the gel during the stretching process, thereby improving the mechanical properties of the gel.

[0066] Comparative Example 2

[0067] Zinc sulfate was dissolved in deionized water to prepare a zinc sulfate solution with a concentration of 2 mol / L, which was used as the liquid electrolyte of the aqueous zinc ion battery. Conventional glass fiber was used as the separator to assemble a liquid Zn-Zn symmetric battery for electrochemical cycle stability performance testing.

[0068] The results are as follows Figure 8 and Fig. 9 As shown, among which, Figure 8 As shown, at 1 mA cm -2 The current density and 1 mAh cm -2 At a capacity density of , the symmetrical battery can be stably cycled for 220 hours. After 220 hours, the battery loses stability due to the growth of zinc dendrites and side reactions; Fig. 9 As shown, at 5 mA cm -2 The current density and 5 mAh cm -2 At a capacity density of , the aqueous symmetrical battery short-circuited after 60 hours of cycling and the battery failed.

[0069] Furthermore, 2 mol / L zinc sulfate was used as the aqueous zinc ion battery liquid electrolyte, conventional glass fiber was used as the separator, zinc foil was used as the negative electrode, and copper foil was used as the positive electrode to assemble a liquid Zn-Cu battery for electrochemical performance testing. The test results are as follows: Fig.10 As shown, according to its calculation, the coulombic efficiency of the liquid Zn-Cu battery after 40 cycles is 31.50%.

[0070] Furthermore, the liquid Zn-Cu battery of Comparative Example 1 was compared with the Zn-Cu battery of Example 3 by cyclic voltammetry test, with the parameters set at -0.2V-0.6V and the scanning speed at 1mV s -1 , the test results are as follows Fig.11 As shown, it can be seen that the nucleation overpotential of the battery using boron nitride nano-localized gel electrolyte is about 67mV, which is much larger than the nucleation overpotential of the aqueous battery (37mV). A higher nucleation overpotential means that a higher potential difference is required to cause the substance to undergo redox reaction on the electrode surface, so more energy is required to form crystal nuclei of zinc ions and deposit them uniformly on the negative electrode. In this case, the solid-state diffusion current density of zinc ions is small, which is conducive to the formation of a uniform deposition layer. On the contrary, a lower nucleation overpotential means that redox reactions can be promoted by a lower potential difference. This may lead to rapid zinc deposition, causing smaller crystal nuclei to grow continuously and branch out from each other to form dendrite growth. Therefore, in terms of nucleation kinetics, gel electrolytes can effectively inhibit the growth of new dendrites.

[0071] It can be seen from the above comparative examples that the gel electrolytes obtained in Examples 1-3 of the present invention can significantly improve the cycle performance of zinc ion batteries.

[0072] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a boron nitride nano-localized gel electrolyte, characterized in that: It includes the following steps: (1) mixing hydroxylated boron nitride nanosheets with water and uniformly dispersing them by ultrasonication to obtain a hydroxylated boron nitride dispersion having a mass concentration of 0.1-0.3 mg / mL; (2) adding monomers, zinc salt, initiator, crosslinking agent and catalyst to the hydroxyboron nitride dispersion to obtain a mixed solution, and adjusting the pH of the mixed solution to 4.0-5.0 to obtain a gel prepolymer solution; (3) heating the gel prepolymer solution to polymerize at 35-45° C. to obtain the boron nitride nano-localized gel electrolyte; Wherein, the monomer is selected from one or more of acrylamide, acrylic acid, methacrylic acid, acryloyloxyethyltrimethylammonium chloride, and 2-acrylamide-2-methylpropanesulfonic acid, and the concentration of the zinc salt is 0.5-2 mol / L.

2. The preparation method according to claim 1, characterized in that: in, The zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc acetate, zinc nitrate and zinc perchlorate.

3. The preparation method according to claim 1, characterized in that: The initiator is ammonium persulfate and / or potassium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide and / or ethylene glycol diacrylate.

4. The preparation method according to claim 1, characterized in that: The mass of the monomer is 10-20 wt % of the mass of the gel prepolymer solution.

5. The preparation method according to claim 1, characterized in that: in, The monomers include anionic monomers, cationic monomers and acrylic monomers. The anionic monomer is 2-acrylamide-2-methylpropane sulfonic acid, the cationic monomer is acryloyloxyethyltrimethylammonium chloride, and the acrylic monomer is one or more of acrylamide, acrylic acid and methacrylic acid.

6. The preparation method according to claim 1, characterized in that: The preparation of the hydroxylated boron nitride nanosheets comprises: ball-milling micron-sized boron nitride powder and sodium hydroxide aqueous solution, washing the ball-milled product with water, ultrasonically dispersing and centrifuging, and then freeze-drying to obtain the hydroxylated boron nitride powder, the particle size of which is 150-250 nm.

7. The preparation method according to claim 1, characterized in that: The temperature of the heating polymerization is 40° C. and the time is 6-12 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The pH is adjusted by the content of the catalyst, and the catalyst is N,N,N',N'-tetramethylethylenediamine.

9. The boron nitride nano-localized gel electrolyte prepared by the preparation method according to any one of claims 1 to 8.

10. A zinc ion battery comprising the boron nitride nano-localized gel electrolyte according to claim 9.

Citation Information

Patent Citations

  • Application of functionalized boron nitride as electrolyte additive, aqueous electrolyte and zinc ion battery / capacitor

    CN114843626A

  • Gradient distribution gel electrolyte, preparation method thereof and application of gradient distribution gel electrolyte in zinc-air battery

    CN117004162A